2022
DOI: 10.1080/15476286.2022.2139110
|View full text |Cite
|
Sign up to set email alerts
|

PRKCE non-coding variants influence on transcription as well as translation of its gene

Abstract: Untranslated regions of the gene play a crucial role in gene expression regulation at mRNA and protein levels. Mutations at UTRs impact expression by altering transcription factor binding, transcriptional/translational efficacy, miRNA-mediated gene regulation, mRNA secondary structure, ribosomal translocation, and stability. PKCε, a serine/threonine kinase, is aberrantly expressed in numerous diseases such as cardiovascular disorders, neurological disorders, and cancers; its probable cause is unknown. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…The rs11573156 SNP is located in the 5’ untranslated region (5’-UTR) of the PLA2G2A gene, acting as a TF binding site that regulates mRNA expression [37]. The current study revealed this region containing rs11573156 is a crucial SP1 binding site that modulates PLA2G2A transcript levels.…”
Section: Discussionmentioning
confidence: 77%
“…The rs11573156 SNP is located in the 5’ untranslated region (5’-UTR) of the PLA2G2A gene, acting as a TF binding site that regulates mRNA expression [37]. The current study revealed this region containing rs11573156 is a crucial SP1 binding site that modulates PLA2G2A transcript levels.…”
Section: Discussionmentioning
confidence: 77%
“…In the case of cancer non-coding SNPs, localization within the UTRs is considered to be especially damaging. The identified variations in these regions are found to perturb the structure of miRNA and thereby the interactions with other miRNAs and gene products [34][35][36]. UTRs maintain post-translation regulation in gene expression, any variation in the UTR region can be linked to severe pathologies [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, genotype association studies for other PKC isoforms with cancer susceptibility have been conducted, indicating the pathogenic effect of certain SNPs [19,20]. Recently, the pathogenic SNPs in PKCε were also predicted through bioinformatics tools that indicated its missence SNPs pathogenicity and potential impact on the structure and function of PKCε protein and non-coding variants impact on the gene expression of the protein [21,22].…”
Section: Introductionmentioning
confidence: 99%